Chicago Unions Building a Left-Labor-Community Coalition, United Working Families, to Restore Working-Class Democracy. (December 2019) - Farmer, Stephanie; Noonan, Sean
Neoliberal political institutions are beholden to the interests of capital and professional classes, leaving working people and communities of color without a voice to shape priorities that benefit their interests. To counteract this elite-dominated political system, the Service Employees International Union Health Care Indiana and Illinois (SEIU-HCII) and the Chicago Teachers Union (CTU), worked with community organizations to form the United Working Families (UWF) Party of Illinois in 2014. UWF is a model of labor-led working class organizing in the electoral system. UWF brings together a left-labor-community alliance under an independent political party formation to champion a left-wing social democratic platform to empower working class people in their workplaces and communities, and to fight against Black and Brown oppression. UWF has provided leadership trainings for a cadre of working class, people of color and women and has been successful electing their leaders to municipal, county and state level government offices.